A Critical Study On Ghaybah Of Imam Mahdi Concept In Shi’ah Imamiyah Ithna ‘Ashariyyah - M Kholid Muslih; Ahmad Tauhid Mafaza; Amir Sahidin (Jurnal Ushuluddin, 2021)
The debate over whether the teachings of the Imāmah Shī'ah Imāmiyah Ithnā 'Ashariyah, including the teachings of the Prophet Muhammad, cannot be avoided. Both SAW the need for Imamat as a substitute for the position of the prophet in managing religion and the world. However, there are fundamental differences that cannot be tolerated, according to ahl sunnah (Sunni), Imāmah is fardhu kifayah, while according to Shī'ah Imāmiyah, it is one of the principles of faith that must be believed. This Shī'ah belief also experienced a deadlock due to the polemic whether Imam al-Ḥasan al-'Ashkari had descendants or not. This deadlock was answered by them by bringing up a new concept in aqidah, called Ghaybah. Therefore, the author sees the need to critically examine this concept of ghaybah, because it is the foundation of the building of the Imamate that is believed to be. In addition to strengthening the faith of Muslims (Sunni), this study will also examine how strong the argument for the concept of ghaybah is. Through a study of the type of library research with a descriptive-critical analysis approach, it can be concluded, first, that the concept of ghaybah does not have a strong argumentative basis. Second, the figure of Imam Mahdi who they believed was only a fictitious figure. Third, the essence of Imam Mahdi's ghaybah contradicts the hadiths of the Prophet SAW and statements of the Shi'ah scholars themselves